2014
DOI: 10.1037/a0036457
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the etiology of psychopathic traits in youth.

Abstract: Few studies have examined the etiology of psychopathic traits in youth, and even fewer have tested whether the genetic and environmental influences underlying these traits differ for boys and girls. We tested for sex differences in the etiology of 3 trait dimensions-impulsivity, narcissism, and callous-unemotionality (CU)-previously found to underlie youth psychopathy in our sample. Using biometric modeling we tested whether constraining the genetic and environmental influences for each dimension across sex re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Similar to Ficks et al [25], our univariate analyses indicated that genetic and shared environmental influences primarily explained the variance in the callous–unemotional dimension, and that a large genetic influence was important for impulsive–need for stimulation. We also found that genetic and shared environmental influences explained the variances in grandiose–deceitful, whereas Ficks et al found that mainly genetic influences were important for narcissism.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to Ficks et al [25], our univariate analyses indicated that genetic and shared environmental influences primarily explained the variance in the callous–unemotional dimension, and that a large genetic influence was important for impulsive–need for stimulation. We also found that genetic and shared environmental influences explained the variances in grandiose–deceitful, whereas Ficks et al found that mainly genetic influences were important for narcissism.…”
Section: Discussionsupporting
confidence: 84%
“…As genetic influences on psychopathic personality traits may vary across the ways in which these traits are measured, in terms of both informant and instrument used [69], more research examining the genetic and environmental etiology of these traits in early childhood is warranted. Also, Ficks et al [25] age-corrected their data (age range 4.4–17.8 years), whereas we used a sample of 5-year-old twins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, reflecting heterotypic continuity, psychopathic traits in girls may represent a latent construct of broader emotion dysregulation and negative emotionality, consistent with evidence of somatization being more strongly linked to secondary psychopathy in girls than in boys (Lilienfeld & Hess, 2001). Although genetic and environmental influences on psychopathic traits may be comparable in boys and girls (Ficks, Dong, & Waldman, 2014), other putative causal risk factors may be divergent (Krischer & Sevecke, 2008; see Verona & Vitale, 2006 for review). Reduced skin conductance responses were positively associated with the interpersonal facet of psychopathic traits (including narcissism) in boys but not girls during a countdown task (Isen et al, 2010).…”
mentioning
confidence: 99%
“…Evidence supports a lower heritability of psychopathic traits [1820] as well as a greater role of family-related risk factors in girls than in boys [21]. However, according to a recent study by Ficks et al [22], the etiology of psychopathic traits in youth seems to be highly similar for girls and boys.…”
Section: Introductionmentioning
confidence: 99%